PENGARUH PENERAPAN GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Roudhatul Amalia; Muhammad Riza Hafizi; Arif Mubarok (Accounting Journal of Ibrahimy (AJI), 2024)
This study aims to analyze the effect of green accounting and environmental performance on the profitability of mining companies listed on the Indonesia Stock Exchange. The population of this study comes from mining companies listed on the Indonesia Stock Exchange. Through the publication of the Indonesia Stock Exchange. Secondary data is taken in annual time series from 2018-2022. At least, the data that can be analyzed further is 55 data. Sample selection is done by purposive sampling method. Data analysis using panel data regression with Eviews 12. The results showed that green accounting has a positive and significant effect on profitability. While environmental performance has no effect on profitability. This study also obtained results showing that green accounting and environmental performance simultaneously have a significant effect on profitability. The R-square value is 56.2%. Therefore, profitability is influenced by green accounting and environmental performance by. While the remaining 43.8% is influenced by other variables outside this study.